Clinical predictors and angiographic features of acute coronary syndromes caused by systemic embolism. (25th November 2020) - Jeronimo Baza, A; Salazar, C; Perez Vyzcaino, M.J; Nombela, L; Jimenez Quevedo, P; Nunez, I; Salinas, P; Mejia, H; Escaned, J; Fernandez Ortiz, A; Ferrandez Escarabajal, M; Martinez Gomez, E; et al.
Abstract: Introduction: Systemic embolism to coronary arteries is one of the mechanisms of acute myocardial infarction (AMI) of non-atherosclerotic cause. However, its clinical profile has not been properly established yet. Purpose: To identify clinical predictors and angiographic characteristics of acute coronary syndromes caused by systemic embolism to a principal coronary artery (ACS-E), as well as to describe in-hospital mortality of these patients. Methods: 40 patients with ACS-E, admitted between 2003 and 2018 in a tertiary hospital. Epidemiological, clinical and angiographic characteristics of these cases were compared with those from 4989 patients, attended for acute coronary syndrome of atherosclerotic cause (ACS-A) in the same hospital during the same period. Results: Patients with ACS-E were younger (28% vs 10% were <45 years old, p<0.001) and had a higher proportion of women (43% vs 22%, p 0.003), atrial fibrillation (40% vs 5%, p<0.001) and neoplasia (18% vs 7%, p 0.009). They had also undergone previous valvular surgery more frequently than patients with ACS-A (13% vs 0.5%, p<0.001) and a higher proportion of them were under treatment with warfarin (15% vs 3%, p<0.001). Variables identified as independent predictors of ACS-E in the multivariate analysis are shown in the table. Regarding clinical presentation, ST elevation AMI was more frequent in ACS-E cases (83% vs 67%, p 0.04). Patients with ACS-E did not present any significative stenosis in other vessels apart from the culprit one (number of other vessels with at least 1 severe stenosis was 0 in the ACS-E group vs 1.33 + 1 in the ACS-A arm, p<0.001). PCI was attempted in 75% of the patients with ACS-E, resulting successful in 80% of the cases. On the other hand, 100% of SCA-A underwent PCI, with a success proportion of 99% (p<0.001). In-hospital mortality in ACS-E group was 15% and 4% in the control group (p<0.001). Conclusions: ACS-E and ACS-A have different clinical and angiographic features. Atrial fibrillation, chronic warfarin treatment, previous valvular surgery, presence of any neoplasia and female sex are independent predictors for ACS-E. Funding Acknowledgement: Type of funding source: None